2019
DOI: 10.1111/pbi.13167
|View full text |Cite
|
Sign up to set email alerts
|

Updates on molecular mechanisms in the development of branched trichome in Arabidopsis and nonbranched in cotton

Abstract: Summary Trichomes are specialized epidermal cells and a vital plant organ that protect plants from various harms and provide valuable resources for plant development and use. Some key genes related to trichomes have been identified in the model plant Arabidopsis thaliana through glabrous mutants and gene cloning, and the hub MYB ‐ bHLH ‐ WD 40, consisting of several factors including GLABRA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
115
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(120 citation statements)
references
References 191 publications
(236 reference statements)
4
115
0
1
Order By: Relevance
“…The growing body of research suggested that phytohormones play significant roles in trichome initiation, development, and density regulation by mediating downstream genes [53]. Gibberellin and jasmonic acid exhibited a synergistic effect on trichome production, and the effect of these two phytohormones reflected an increased proportion of cells that developed into trichomes, despite an increase in the overall epidermal cell number of the leaves in Arabidopsis [54].…”
Section: The Differential Expression Patterns Of Unigenes In Differenmentioning
confidence: 99%
“…The growing body of research suggested that phytohormones play significant roles in trichome initiation, development, and density regulation by mediating downstream genes [53]. Gibberellin and jasmonic acid exhibited a synergistic effect on trichome production, and the effect of these two phytohormones reflected an increased proportion of cells that developed into trichomes, despite an increase in the overall epidermal cell number of the leaves in Arabidopsis [54].…”
Section: The Differential Expression Patterns Of Unigenes In Differenmentioning
confidence: 99%
“…Thus, Arabidopsis could serve as a model for elucidating the genetic mechanisms controlling cotton ber development [31][32]. Many genes were identi ed by homoeologous cloning and con rmed to be related to ber development [2]. There has been long-standing interest in whether the genetics of simply inherited traits, such as trichomes in cotton, could increase our understanding of more complex processes, such as lint ber development [31,33].…”
Section: Stem Trichomes and Seed Bers Are Epidermal Hairs That Are Rementioning
confidence: 99%
“…Their easy manipulation and observation made plant trichomes ideal for studying cell differentiationrelated pathways [2][3]. The trichomes of Arabidopsis thaliana have a specialized unicellular structure and are 200-500 µm in length.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cotton is an important economic crop that provides ber for textile industry. Cotton ber is a single cell differentiated from the epidermal ovule, and its development consists of four overlapping stages including ber initiation, elongation, second cell wall biosynthesis and maturation [12], which are regulated by many genes [13]. For instance, GbMYB2 was speci cally expressed in the epidermal layer of ovule and bers, and overexpression of GbMYB2 in Arabidopsis displayed enhanced trichromes growth on leaves and longer roots [14].…”
Section: Introductionmentioning
confidence: 99%